Religious festivals and economic development: Evidence from the timing of Mexican saint day festivals - Montero, Eduardo and Yang, Dean (The American Economic Review)
Does variation in how religious festivals are celebrated have economic consequences? We study the economic impacts of the timing of Catholic patron saint day festivals in Mexico. For causal identification, we exploit cross-locality variation in festival dates and in the timing of agricultural seasons. We estimate the impact of "agriculturally coinciding" festivals (those coinciding with peak planting or harvest months) on long-run economic development of localities. Agriculturally coinciding festivals lead to lower household income and worse development outcomes overall. These negative effects are likely due to lower agricultural productivity, which inhibits structural transformation out of agriculture. Agriculturally coinciding festivals may nonetheless persist because they also lead to higher religiosity and social capital.- Reproduced